CYP19A1 rs2470152 polymorphism increases susceptibility to depression in Chinese Han population. (20th November 2019) - Yang, Yanping; Yan, Huacheng; Kong, Yanying; Liu, Lebin; Peng, Qiuju; Wen, Yuguan; Zhou, Zhijian; Chang, Qingxian
Highlights: Correlation between CYP19A1 polymorphism and depression investigated in Han Chinese. rs2470152 in the recessive model (AA vs . GG + GA) increased the risk of depression. No gender-related risk differences were found between patients and controls. CYP19A1 rs2470152 polymorphism is a risk factor for depression pathogenesis. Abstract: Estrogen plays a vital role in the pathogenesis of depression. The cytochrome p450 (CYP) 19A1 gene encodes aromatase, which is responsible for a key step in estrogen production. Previous studies suggested that CYP19A1 polymorphisms increase the risk of depression in the Japanese population. The current study aimed to investigate the correlation between the CYP19A1 rs2470152 polymorphism and the risk of depression in Chinese Han population. In total, 1006 Chinese Han subjects were recruited in this case-control study, including 502 patients diagnosed with depression and 504 healthy gender- and age-matched (from 18–65 years) controls. Genotyping was performed using multiplex PCR and high-throughput sequencing to assess the effects of the CYP19A1 rs2470152 (G > A) polymorphism on the risk of depression in the entire cohort and the subjects were further stratified by gender. No significant differences were observed in allele and genotype frequencies of CYP19A1 rs2470152 between total cases and controls (P > 0.05). However, the CYP19A1 rs2470152 polymorphism in the recessive model (AA vs . GG + GA) was associated with increased risk of depression (χ 2 = 4.077, P = 0.043, OR = 1.347, 95% CI = 1.008–1.798). After subjects stratification by gender, neither genotypes nor genetic models showed significant differences between cases and controls (all P > 0.05). The results indicated that the CYP19A1 rs2470152 (G > A) polymorphism in the recessive model (AA vs . GG + GA) was correlated with increased risk of depression in Chinese Han population.